Efficient tax competition under the origin principle. (26th June 2017) - Gauthier, Stéphane
Abstract: This paper studies fiscal competition under the origin principle. It identifies a pattern of consumers' taste heterogeneity under which the first‐best world social optimum arises as a noncooperative Nash equilibrium. Consumers' tastes are characterized by the strength of their preference for home and foreign goods. Nash implementation of the first‐best obtains when in every tax jurisdiction the number of consumers who display a home bias (those consumers who prefer purchasing the home good to shopping abroad at equal prices) equals, for every magnitude of the home bias, the number of consumers who display an "import bias" (those who instead prefer shopping abroad) equal in magnitude.